Shared Leadership and its Relationship with the Organizational Culture of Secondary School Leaders at General Education Schools - Alfahhad, Abdullah Musfeer Molfi; Alshamrani, Hamed Mohammed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the shared leadership and its relationship to the organizational culture of secondary school leaders in general education schools, and to identify whether there are statistically significant differences between the averages of the study variables to the variables (education, specialization, years of service) in public education schools in Najran region. the researcher followed the descriptive survey method due to its relevance to the nature of the study, and the use of the questionnaire tool to collect study data. The research population consisted of all secondary school teachers in the Najran region for the academic year 1443 H, totaling (2056) teachers. The researcher used the (available) sample method where an electronic link was made and circulated to the target group of parameters, and after determining the duration of the responses represented by two weeks to receive the responses, their number was (788) teachers and a percentage of (38.3%) of the study population.The study found these results: 1- The overall mean of the degree of secondary school leaders’ practice of the dimensions of shared leadership (delegation of authority, participation in decision-making, human relations) in Najran region from the teachers’ point of view was (4.37) , Human relations came in the first place with an arithmetic mean (4.38) , decision-making came in the second place with a mean (4.37) , and the arithmetic mean of the dimension of delegation of authority was (4.35). 2- The overall degree of the level of organizational culture prevailing among secondary school leaders in Najran region from the teachers’ point of view was (4.37) , and the first dimension of organizational values ranked third with A mean (4.36) , the second dimension is beliefs Organizational norms ranked first with a mean (4.38) , the third dimension, organizational norms, ranked third, with a mean (4.36) , the fourth dimension, organizational expectations, ranked second with a mean (4.37).3- There are statistically significant differences between the averages of the study variables to the degree of high school leaders’ practice of shared leadership and the dimensions of organizational culture due to the variables (scientific qualification, specialization, years of service) in public education schools in Najran, especially in favor of the humanities and natural sciences majors, and in favor of degree holders Bachelor’s and Ph.D., and for the benefit of those who have served (1-7) years, and for those who have served (15) years or more.Based on the results of the study, the researcher recommended the necessity of strengthening shared leadership practices among school leaders through training courses and special conferences, giving more attention to their application, preparing and preparing future leaders, and working to raise awareness among workers in public education schools about the importance of shared leadership and its role in Strengthening the organizational culture of employees.
Keywords: leadership; shared leadership; organizational culture; decision-making; delegation of authority; human relations